Parent’s Rational Choices in the Practice of Feeding Stunted Toddlers in Tegal Regency - Fikri Afrilia Rizky; Nurhadi Nurhadi; Riadi Syafutra Siregar (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
Stunting is a failure in children’s growth. Stunting indicates that nutritional intake in children is not fulfilled properly. This research aims to describe what kind of rational choices are applied in feeding stunted toddlers by the Parents. The research method used is a phenomenological-type descriptive qualitative. The results of this research discuss the rational choices in feeding practices such as spiritual knowledge that are taught by parents to toddlers before eating, the practice of cooking and feeding the children, the strategies used when children have no interest in eating, and the activities implemented in dealing with stunting. Rational choice has two elements: the role of actors, which are parents, especially mothers, and resources, namely the mothers’ ability to implement feeding practices.  Mothers’ practices in feeding stunted toddlers are based on rational considerations so children's nutrition can be adequately fulfilled.